Relative contribution of anthropogenic warming to the unprecedented heatwave in South America in 2023 - Congren Li; Xiaojing Yu; Jianghua Zheng; Mingjiang Deng; Wanqiang Han; Ping Ma (npj Climate and Atmospheric Science)
Abstract In 2023, South America experienced an unprecedented heatwave that threatened socioeconomic structures and ecosystems. This study uses attribution analysis to evaluate the contributions of atmospheric circulation patterns and human factors to the heatwave's probability and intensity. The 2023 heatwave is a 1-in-130-year event and a 1-in-65-year event, with and without considering the 2023 heatwave in the fitting, respectively. The large-scale meteorological analysis revealed that the heatwave was driven by an anomalously high-pressure system that formed a heat dome from dry, hot air columns. ALL (all-forcing scenario) and GHG (greenhouse gas scenario) simulations indicate the likelihood of future extreme heatwaves increases by 28.45% [27.60%, 29.30%] (90% confidence interval) and 30.42% [29.51%, 31.33%] (90% confidence interval), respectively, based on data from 1850 to 2014. Insights from Coupled Model Intercomparison Project Phase 6 (CMIP6) models emphasize that human-induced warming significantly contributes to heatwaves, which highlights the need for effective climate adaptation and mitigation strategies.